OVERCOMING INCUMBENT CHALLENGES TO BUSINESS MODEL INNOVATION. Issue 91 (18th October 2018) - Johnson, Mark W.
Abstract: Business model innovation is a hot topic these days, but Johnson has been working in and writing about it for years. Here he explains "white space pursuits, " which he describes as "venture[s] into markets that the company hasn't served before, with new and different products and services." He illustrates how companies such as Sony and Kodak held on too long to what became outdated models. Leaders can inform relevant stakeholders and place potential innovations in context, "describing the threats and opportunities they are facing that are impelling them to move past their core and its adjacencies, and explaining why remaining too close to home is actually a greater risk than a well‐managed trip into the white space."